2022
DOI: 10.3390/ma15114016
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Enhanced Thermoelectric Performance in GeS2 Monolayer

Abstract: Strain engineering has attracted extensive attention as a valid method to tune the physical and chemical properties of two-dimensional (2D) materials. Here, based on first-principles calculations and by solving the semi-classical Boltzmann transport equation, we reveal that the tensile strain can efficiently enhance the thermoelectric properties of the GeS2 monolayer. It is highlighted that the GeS2 monolayer has a suitable band gap of 1.50 eV to overcome the bipolar conduction effects in materials and can eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…Gao 等人研究了 Pd 修饰 GeS 2 单层的吸附 行为及电子、光学和气敏特性 [25]. Ruan 等人研究发现拉伸应变可提高单层 GeS 2 的热电性能 [26] . Mao 等人研究了双层 GeS 2 在外加电场和应变下对其结构、电子和光学性质的影响 [27] .…”
Section: 引言 最近研究表明 通过堆叠两种或更多不同的二维 ( 2d ) 材料构建范德华异质结 ( Vdwhs )unclassified
“…Gao 等人研究了 Pd 修饰 GeS 2 单层的吸附 行为及电子、光学和气敏特性 [25]. Ruan 等人研究发现拉伸应变可提高单层 GeS 2 的热电性能 [26] . Mao 等人研究了双层 GeS 2 在外加电场和应变下对其结构、电子和光学性质的影响 [27] .…”
Section: 引言 最近研究表明 通过堆叠两种或更多不同的二维 ( 2d ) 材料构建范德华异质结 ( Vdwhs )unclassified
“…10,11 In addition to the application environments of devices, strain engineering, as the simplest adjustment method, has been widely used in the regulation of the thermoelectric properties of two-dimensional materials. [12][13][14] In particular, recent studies have shown that for monolayer HfSe 2 , the optimal thermoelectric figure of merit ZT max can be increased from 0.16 to 2.41 under p-type doping and 0.53 to 1.91 under n-type doping by strain engineering. 15 The good tunability of the thermoelectric properties of monolayer HfSe 2 indicates that it has great application potential in the field of thermoelectricity.…”
Section: Introductionmentioning
confidence: 99%